2013
DOI: 10.4236/jsea.2013.612076
|View full text |Cite
|
Sign up to set email alerts
|

Prelude to <i>Natphoric Kansei </i> Engineering Framework

Abstract: Consumers' emotion has become imperative in product design. In affective design field, Kansei Engineering (KE) has been recognized as a technology that enables discovery of consumer's emotion and formulation of guide to design products that win consumers in the competitive market. Albeit powerful technology, there is no rule of thumb in its analysis and interpretation process. KE expertise is required to determine sets of related Kansei and the significant concept of emotion. Many research endeavours become ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Finally, researchers use intelligent algorithms to train and optimize models to guide subsequent design. These methods include deep learning [31], swarm intelligence algorithms [32], genetic algorithms [33], and a combination of multiple optimization methods [34,35].…”
Section: Kansei Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, researchers use intelligent algorithms to train and optimize models to guide subsequent design. These methods include deep learning [31], swarm intelligence algorithms [32], genetic algorithms [33], and a combination of multiple optimization methods [34,35].…”
Section: Kansei Engineeringmentioning
confidence: 99%
“…Finally, researchers use intelligent algorithms to train and optimize models to guide subsequent design. These methods include deep learning [31], swarm intelligence algorithms [32], genetic algorithms [33], and a combination of multiple optimization methods [34,35]. Therefore, the KE method is used to collect case samples and image vocabulary to form an initial sample set and an initial image set in this paper.…”
Section: Kansei Engineeringmentioning
confidence: 99%
“…This study adopts method of Kansei Engineering Type I (KEPack) due to its simplicity and wide use in many product developments [2,6,10,19,20,22,23]. Figure 3 shows the systematic processes of KEPack.…”
Section: Kepackmentioning
confidence: 99%
“…Other studies of Kansei engineering in e-Learning can be found in [19] which reports about Kansei semantic space in online database courseware systems and [20] which reports a theoretical framework of playful interaction in mobile learning system. Chen [21], Hussin and Lokman [22], and Lokman [23] are other studies of Kansei engineering to design an interface of web-based system development.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study used the theory of Kansei engineering and the multidimensional scaling algorithm to study subjects' "perception" cognition rules of products [6,7,8]. Furthermore, we discussed the perception quantification method of product form and affirmed the relation between "perception" and product design, with the establishment of the effective mapping relation between perceptual words and design elements.…”
Section: Introductionmentioning
confidence: 99%